Metabolomics of Lyme patients using NMR spectroscopy and biomarker analysis - Saravanan, Elanthiraiyan (2018)
Lyme disease (LD) is one of the dreadful tick-borne diseases. It is commonly caused by pathogen Borrelia burgdorferi and three different species of Borrelia. Number of LD cases being reported each year is increasing drastically in various parts of the world. Although history of LD dates back to late 1970s, LD diagnosis and treatment is yet a challenging task. The existing, Centers for Disease Control and Prevention (CDC) and Food and Drug Administration (FDA) approved serological diagnostic methods of LD diagnosis show low assay sensitivity. The sensitivity of the serological based LD diagnostic techniques is less than 69 % for early or acute LD diagnosis. Therefore, there is an immense need for more sensitive diagnostic method. LD pathogens interact with various types of cells within the body such as neurons, muscle fibers, etc. The pathogens primarily disturbs the cellular pathways which causes fluctuations in the levels of metabolites, including the levels of amino acids. We used nuclear magnetic resonance spectroscopy (NMR) which is one of the promising techniques for omics studies, to detect and quantify metabolites in LD patient sera. We observed a strict elevation in the level of lactate and decrease in the level of glucose, choline and alanine in majority of acute and late LD patients sera used in this study. Statistical modeling and results suggest that based on the identified features acute and late LD patients can be distinguished from the healthy donors with sensitivity 80 % and specificity 90 - 100 %. Notably, 89 % of the CDC negative lyme samples were correctly classified based on the identified features. Our results suggest that metabolic profiling of LD patients could be a better alternate for both acute and late LD diagnosis with improved sensitivity, compared to expensive serological techniques.